(untitled) (Northern International Medical College Journal, 2018)
Background : Hypertensive disorders are the most common medical complications during pregnancy and are associated with high maternal and fetal mortality and morbidity.Half of the pregnant women with hypertension have preeclampsia. Association of low serum calcium level with preeclampsia(PE) is known decades together. Objectives : To assess serum calcium level in mild and severe preeclampsia(PE). Materials and Method : This was a comparative cross sectional study conducted in the department of Obstetric and Gynaecology, Combined Military Hospital (CMH),Dhaka, Bangladesh. The data were collected from 50 mild preeclampsia and 50 severe preeclampsia patients admitted in Obstetric and Gynaecology ward of CMH who fulfill the inclusion criteria. Study period was July 2015 to December 2015. Serum calcium was measured in Auto analyzer machine in the clinical pathology of Armed forced Institute of pathology (AFIP). Data were analyzed by statistical software, SPSS version 20. Results : Serum calcium level was found in severe PE was 8.12mg/dl and in mild PE was 8.85mg/dl. Study also reveals that routine calcium supplementation was consumed less in severe PE than mild PE patients. Conclusion : Serum calcium is markedly reduce in severe preeclampsia than in mild preeclampsia. Therefore routine examination of serum calcium level may be useful as diagnostic marker in high risk pregnancy. Northern International Medical College Journal Vol.9(1) July 2017: 255-257